A Single-Phase Battery Charger Design for LEV Based on DC-SRC With Resonant Valley-Fill Circuit - Lee, Jun-Young; Yoon, Young-Doo; Kang, Jung-Won (IEEE transactions on industrial electronics (1982), 2015)
This paper suggests a single-phase and single-stage battery charger for a light electric vehicle to improve the lifetime by removing high voltage electrolytic capacitors. The proposed charger is based on a diode-clamped series resonant converter equipped with a resonant valley-fill circuit, which increases the power factor by removing dead zones in the line current and reduces the switching loss of the valley-fill circuit. The feasibility of the proposed charger has been verified with a 1.7-kW prototype.